The Strategic Role of the TNI in Preventing the Development of Radicalism in Indonesia in the Perspective of Law 34 of 2004 - Suharyanto, Suharyanto; Sugianto, Sugianto (Jurnal Legisci, 2024)
In the Law of the Republic of Indonesia number 3 of 2002 concerning national defense, it is said that national defense is prepared early to face existing threats. The purpose of state defense is to maintain and protect state sovereignty, maintain the territorial integrity of the Republic of Indonesia, and maintain the safety of the entire nation from all forms of threats both from outside and from within the country. The threats in question are divided into 3: military, non-military, and hybrid. Meanwhile, according to the priority scale, threats are divided into 2: actual threats and potential threats. One of the actual threats that occur in Indonesia can be seen from the problems of terrorism and radicalism that still often occur in various regions and communities in Indonesia. In the Law of the Republic of Indonesia number 34 of 2004, it is stated that the TNI in carrying out its primary duties is carried out through war military operations and military operations other than war, where in more detail in article 7 paragraph (2) point (b) states that one of the military operations other than war (OMSP) is to overcome acts of terrorism, which according to the Center for Studies The TNI strategy in its study on the role of the TNI in preventing the development of radicalism, terrorism is deeply rooted in radicalism.